2005
DOI: 10.1602/neurorx.2.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Small molecular drug transfer across the blood-brain barrier via carrier-mediated transport systems

Abstract: Summary:Because of the physiological nature of the bloodbrain barrier (BBB), transport of chemical compounds between blood and brain has been widely believed to occur by means of passive diffusion, depending upon the lipophilicity of the compounds. However, discrepancies exist between the lipophilicity and apparent BBB permeation properties in many cases, and these discrepancies can be ascribed to the existence of multiple mechanisms of drug transport through the BBB. Molecular identification and functional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 71 publications
(49 reference statements)
1
83
0
9
Order By: Relevance
“…Significant deviations from the above parabolic relationship have been found, which can be ascribed to the existence of multiple mechanisms of drug transport through the BBB [143] . There is clear evidence that the expression of active efflux pumps like the multidrug transporter P-glycoprotein (P-gP) at the BBB accounts for the poor permeability of certain drugs (see below).…”
Section: Physicochemical Characterization Of Lead Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant deviations from the above parabolic relationship have been found, which can be ascribed to the existence of multiple mechanisms of drug transport through the BBB [143] . There is clear evidence that the expression of active efflux pumps like the multidrug transporter P-glycoprotein (P-gP) at the BBB accounts for the poor permeability of certain drugs (see below).…”
Section: Physicochemical Characterization Of Lead Compoundsmentioning
confidence: 99%
“…Furthermore, a variety of nutrient transporters expressed at the BBB are able to transport certain xenobiotics and drugs [141,143] . Recently, it has been shown that the α4β2 …”
Section: Physicochemical Characterization Of Lead Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…E tápanyagok lehetnek cukrok, ketontestek, aminosavak, lipidek, vitaminok, ásványi sók, metabolikus prekurzorok, peptidek, fehérjék. Az agyi endothelsejtek számos ilyen transzportert expresszálnak: az aminosavtranszportban részt vevő SLC3 és SLC7 család tagjait (például L típusú aminosav-transzporter 1), a glükózt transzportáló SLC2-A2 (GLUT-1), a glutamáttranszportban részt vevő SLC1 család tagjait vagy az SLC15 (proton/oligopeptid transzporter -PEPT), az SLC16 (monokarboxilát-transzporter -MCT), az SLC21 (organikus aniontranszporterek -OAT), az SLC22 (organikus anion/kation transzporter -OCT), valamint az SLC44 (kolintranszporter -CTL) család tagjait [1].…”
Section: Abc (Atp-binding Cassette) éS Slc (Solute Carrier) Transzporunclassified